A composite hydrogel with co-delivery of antimicrobial peptides and platelet-rich plasma to enhance healing of infected wounds in diabetes. (1st April 2021) - Wei, Shikun; Xu, Pengcheng; Yao, Zexin; Cui, Xiao; Lei, Xiaoxuan; Li, Linlin; Dong, Yunqing; Zhu, Weidong; Guo, Rui; Cheng, Biao
Abstract: Diabetic wound healing remains a major challenge due to its vulnerability to bacterial infection, as well as the less vascularization and prolonged inflammatory phase. In this study, we developed a hydrogel system for the treatment of chronic infected wounds, which can regulate inflammatory (through the use of antimicrobial peptides) and enhance collagen deposition and angiogenesis (through the addition of platelet-rich plasma (PRP)). Based on the formation of Schiff base linkage, the ODEX/HA-AMP/PRP hydrogel was prepared by mixing oxidized dextran (ODEX), antimicrobial peptide-modified hyaluronic acid (HA-AMP) and PRP under physiological conditions, which exhibited obvious inhibition zones against three pathogenic bacterial strains ( E. coli, S. aureus and P. aeruginosa ) and slow release ability of antimicrobials and growth factors. Moreover, CCK-8, live/dead fluorescent staining and scratch test confirmed that ODEX/HA-AMP/PRP hydrogel could facilitate the proliferation and migration of L929 fibroblast cells. More importantly, in vivo experiments further demonstrated that the prepared hydrogels could significantly improve wound healing in a diabetic mouse infection by regulating inflammation, accelerating collagen deposition and angiogenesis. In addition, prepared hydrogel showed a significant antibacterial activity against S. aureus and P. aeruginosa, inhibited pro-inflammatory factors (TNF-α, IL-1β and IL-6), enhanced anti-inflammatory factors (TGF-β1) and vascular endothelial growth factor (VEGF) production. The findings of this study suggested that the composite hydrogel with AMP and PRP controlled release ability could be used as a promising candidate for chronic wound healing and infection-related wound healing. Graphical abstract: Image, graphical abstract